PKM SOSIALISASI TENTANG MAKANAN PENDAMPING ASI (MP-ASI) SESUAI USIA DAN KONDISI ANAK DI POSYANDU MEKAR DESA BUKIT KEMUNING KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Erma Kasumayanti; Siti Hotna Siagian (Universitas Pahlawan Tuanku Tambusai, 2022)
Meeting nutritional needs can help increase growth and development in infants and children. In fact, many children aged less than two years experience growth and development disorders due to malnutrition from the time they are in the womb, mothers do not give exclusive breastfeeding, give complementary foods too early to breastfeed (MP-ASI) and the MP-ASI consumed by children does not contain enough children's nutritional needs. In the village of Bukit Kemuning it is known that early MP-ASI was given at the age of 0-6 months, besides that the MP-ASI given was not appropriate for the child's age. This socialization and education is provided as an effort to increase public knowledge in the provision of MP-ASI according to the stage and age of the child. This activity was carried out at the Posyandu Mekar, Bukit Kemuning Village, Tapung Hulu District, Kampar Regency on August 16 2022 involving pregnant women, mothers with children under the age of 2, posyandu cadres and professional staff. The number of participants who attended were 45 people. This activity starts from the preparation, implementation and evaluation stages of activities. Based on the results of the activity evaluation, it was found that there was an increase in the knowledge of parents and cadres about education about the provision of MP-ASI according to the age and condition of the child. It is expected that parents can provide MP-ASI according to the recommended age of the child and the MP-ASI given will meet the nutritional needs of the child so that the child's growth and development is normal according to the stages of its development. Keywords: Complementary Food for ASI, Outreach